THE RENAL HANDLING OF HEMOGLOBIN : I. GLOMERULAR FILTRATION - Bunn, H. Franklin (The Rockefeller University Press, 1969)
The glomerular filtration of hemoglobin (α(2)β(2)) was studied under conditions in which its dissociation into αβ dimers was experimentally altered. Rats receiving hemoglobin treated with the sulfhydryl reagent bis(N-maleimidomethyl) ether (BME) showed a much lower renal excretion and prolonged plasma survival as compared with animals injected with untreated hemoglobin. Plasma disappearance was also prolonged in dogs receiving BME hemoglobin. Gel filtration data indicated that under physiological conditions, BME hemoglobin had impaired subunit dissociation. In addition, BME hemoglobin showed a very high oxygen affinity and a decreased rate of auto-oxidation. Glomerular filtration was enhanced under conditions which favor the dissociation of hemoglobin into dimers. Cat hemoglobin, which forms subunits much more extensively than canine hemoglobin, was excreted more readily by the rat kidney. The renal uptake of (59)Fe hemoglobin injected intra-arterially into rabbits varied inversely with the concentration of the injected dose.